2019
DOI: 10.1111/dth.12974
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Therapies for Skin Diseases in Sub‐Saharan Africa

Abstract: Typically, most patients in Nigeria would have tried both oral and topical remedies before visiting a dermatology clinic. There are no documentations of what these remedies are. The aim of this study is to determine what remedies patients use and the influence of age, gender, level of education, and marital status on the choice of herbal remedies. This was a retrospective cross‐sectional chart review over a 3‐year period. Records of all new patients attended to at the dermatology clinic between October 2015 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
6
6
0
Order By: Relevance
“…17 That study also revealed a similar incidence of the use of herbal medication as in this study. 17 A is reported in other authors. 2,5,13,17 The specific diseases for which patients engaged in SM were dermatitis, acne, infections, pigmentary disorders, and urticaria.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…17 That study also revealed a similar incidence of the use of herbal medication as in this study. 17 A is reported in other authors. 2,5,13,17 The specific diseases for which patients engaged in SM were dermatitis, acne, infections, pigmentary disorders, and urticaria.…”
Section: Discussionsupporting
confidence: 84%
“…In consonance with this study, a previous study on indigenous therapy by dermatology patients, revealed the use of mainly Western medications. 17 That study also revealed a similar incidence of the use of herbal medication as in this study. 17 A topical therapy was the predominant form used irrespective of if remedy was herbal or Western.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations